Determinants of proper nutrition behaviors in women: A study based on health promotion model in 2016 - Mohamad Tajfrd; Mohamad Vahedian Shahroudi; Habibollah Esmaily; Nasrin Alizadeh; Zahra Hoseini khabooshan (Mashhad University of Medical Sciences, 2017)
Introduction: Poor eating habits are the cause of 20% cancers in developing countries. Proper nutrition, not smoking and regular physical activity are the main components of prevention of chronic diseases. Therefore, attention to proper nutrition is necessary. This study was performed with aim to evaluate determinants of proper nutrition behaviors in women. Methods: This descriptive cross-sectional study was performed on 365 women aged 18-60 years old at Bojnord in 2016. Data were collected using health promotion model questionnaire. The collected data included individual characteristics, perceived self-efficacy, emotions, perceived benefits, perceived barriers, interpersonal influencers, status influencers, commitment to action plans, and behaviors outcomes. Data were analyzed using SPSS software (version 24) and Independent t, Chi-square, Correlation coefficient, One-way ANOVA, Spearman correlation and linear regression tests. P<0.05 was considered significant. Results: Proper nutrition behaviors in women were significantly associated with the factors such as education (p = 0.04), marital status (p = 0.03) and income level (p <0.0001), while were not significantly associated with employment status (P=0.007). The structures of perceived self-efficacy (p = 0.01), perceived barriers (p = 0.04) and behavioral outcomes (p = 0.002) had significant relationship with proper nutrition behaviors in women. 282 (77.36%) of the studied subjects were self-efficient in their meal plans. Conclusion: The present study showed the effectiveness of health promotion model in predicting proper nutrition behaviors in women, thus, this model can be used as a framework for designing educational interventions.